Given that y = cosh^-1 (x) , Show that y = ln(x+ sqrt(x^2-1))

Have a picture of full working with annotation to go through during interview.Here is rough outline:y = cosh-1(x)x = cosh(y)x = (ey+e-y)/22x = ey+e-yey+e-y -2x = 0Turn into hidden quadratic by multiplying by eye2y-2xey+1=0By quadratic formula:ey = x +/- sqrt(x2-1)Take positive root in order to make inverse function 1 to 1.y = ln(x + sqrt(x2-1)

Related Further Mathematics A Level answers

All answers ▸

solve the equation 4cos^2(x) -15sin(x) = 13


How would you use the Integration Factor method to solve an ordinary first-order linear differential equation?


Given y=arctan(3e^2x). Show dy/dx= 3/(5cosh(2x) + 4sinh(2x))


Find the general solution to the differential equation d^2x/dt^2 + 5 dx/dt + 6x = 4 e^-t


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences